Kinetics of a Collagen-Like Polypeptide Fragmentation after Mid-IR Free-Electron Laser Ablation - Zavalin, Andrey (The Biophysical Society, 2008)
Tissue ablation with mid-infrared irradiation tuned to collagen vibrational modes results in minimal collateral damage. The hypothesis for this effect includes selective scission of protein molecules and excitation of surrounding water molecules, with the scission process currently favored. In this article, we describe the postablation infrared spectral decay kinetics in a model collagen-like peptide (Pro-Pro-Gly)(10). We find that the decay is exponential with different decay times for other, simpler dipeptides. Furthermore, we find that collagen-like polypeptides, such as (Pro-Pro-Gly)(10), show multiple decay times, indicating multiple scission locations and cross-linking to form longer chain molecules. In combination with data from high-resolution mass spectrometry, we interpret these products to result from the generation of reactive intermediates, such as free radicals, cyanate ions, and isocyanic acid, which can form cross-links and protein adducts. Our results lead to a more complete explanation of the reduced collateral damage resulting from infrared laser irradiation through a mechanism involving cross-linking in which collagen-like molecules form a network of cross-linked fibers.